SOCIODEMOGRAPHIC ASPECTS OF CONTRACEPTION USE IN KAMPUNG KB KOTA YOGYAKARTA - Sri Yuni Tursilowati; Bariana Widitia Astuti; Julaikah Julaikah (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
Background: One of the government's efforts to control the population growth rate is to reduce the birth rate through the family planning program by utilizing the contraceptive method.This study aims to analyze the factors that influence contraceptive use at Kampung KB in Yogyakarta Method: It belongs to obsvational research with cross sectional layout using quantitative approach. Sampling was performed using Accidental Random Sampling.Collecting data using online quitioner that was shared to women in reproductive years in all Kampung KB. Data processing using STATA version 14. The data analysis was performed gradually covering univariable analysis, bivariable. Result: Age, education, desire to have children, parity, knowledge and attitudes have the pto increase contraceptive use, while economic level is not positively related to contraceptive use.The reasons for not using contraception are lack of permission from a partner and external environmental pressure. Conclusion: Sociodemographic aspects have the opportunity to increase contraceptive use at Kampung KB in Kota Yogyakarta.